Phase equilibria in the system CaO–SiO2–Nb2O5–La2O3 at 1473 K with pO2=10−15.47 atm. Issue 6 (15th April 2020) - Liu, Chengjun; Qiu, Jiyu; Liu, Zhengyue; Zhu, Deying; Wang, Yeguang
Abstract: Phase equilibria in the CaO–SiO2 –La2 O3 –Nb2 O5 system are important for the utilization of Nb and Rare Earth resources. In the present work, phase equilibria in the CaO–SiO2 –La2 O3 –Nb2 O5 system at 1473 K in H2 (pO2 = 10 −15.47 atm) were studied by the equilibrium experiment. SEM, EDS and XRD analysis were employed to identify the equilibrium phase relations. The isothermal spatial phase diagram of the CaO–SiO2 –La2 O3 –Nb2 O5 system and the isothermal section of CaO–SiO2 –Nb2 O5 -(5%, 10%) La2 O3 pseudo-ternary system were constructed. A total of eight equilibrium phase regions were determined, including Liquid + CaNb2 O6 +CaSiO3 +LaNbO4 region, Liquid + CaNb2 O6 +SiO2 +CaSiO3 region, Liquid + CaSiO3 +CaNb2 O6 region, Liquid + CaSiO3 +SiO2 region, Liquid + CaNb2 O6 +SiO2 region, Liquid + CaSiO3 region, Liquid + SiO2 region and Liquid + CaNb2 O6 region. Additionally, the influence of pO2 on equilibrium composition and temperature was also investigated considering its significant effect on phase equilibria in the slag system with variable valence elements. The results indicated that higher external pO2 can increase the equilibrium O content in a slag system, while higher equilibrium temperature corresponds to higher equilibrium pO2 . Besides, the relationship between phase equilibria shown in the traditional slag system and in the related generalized alloy system was also revealed. The present experimental data can help further study on Nb-bearing and RE-bearing slag systems, and the theoretical conclusions will help the development of thermodynamic models.